1996
DOI: 10.1177/001789699605500111
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change for dietary fat reduction: associations with food intake, decisional balance and motives for food choice

Abstract: The stages-of-change model developed by Prochaska and DiClemente was applied to readiness for dietary fat reduction in a postal survey of adults in South London (N = 366). The percentage of respondents falling into each stage was as follows: precontemplation 35.1, contemplation 12.7, preparation 4.1, action 5.5, and maintenance 42.5. More men than women were precontemplators, while more women were in the maintenance stage. Significant associations with dietary fat consumption were observed, but there was no re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 25 publications
2
47
0
5
Order By: Relevance
“…The relatively small number of subjects were highly motivated, predominantly female, and from non-manual worker households. Such characteristics have been found in other studies (Sigman-Grant, 1996;Steptoe et al, 1996) to be typical of those contemplating dietary change. It has recently become recognised that interventions should be designed to match subjects`stage of change' and, as this intervention was intended to measure the consequences of action, this method was adopted.…”
Section: Discussionsupporting
confidence: 76%
“…The relatively small number of subjects were highly motivated, predominantly female, and from non-manual worker households. Such characteristics have been found in other studies (Sigman-Grant, 1996;Steptoe et al, 1996) to be typical of those contemplating dietary change. It has recently become recognised that interventions should be designed to match subjects`stage of change' and, as this intervention was intended to measure the consequences of action, this method was adopted.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies of the relationships between stages of diet and actual dietary intake have been performed in relation to low-fat diets (24,26) or fruit and vegetable intake (27)(28)(29). Additionally, in this paper, salt intake was not measured by dietary questionnaire, but by a biological measurement of urinary salt.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, users who reported being in the action and maintenance stages for any of the above parameters and presented an inappropriate diet were reclassified into the pseudo-maintenance stage as suggested by Steptoe et al 15 .…”
Section: E T H O D Smentioning
confidence: 99%
“…To solve potential controversies between self-assessment and actual intake, Steptoe et al 15 suggested a reclassification of individuals with the parallel implementation of tools that quantitatively assess food intake. A pseudo-maintenance stage, which includes individuals who are classified in the advanced stages of readiness to change behavior but do not have appropriate food habits, is therefore proposed.…”
Section: Introductionmentioning
confidence: 99%